Genome Sequencing of Ancient Plant Remains: Findings, Uses and Potential Applications for the Study and Improvement of Modern Crops - Di Donato, Antimo; Filippone, Edgardo; Ercolano, Maria R.; Frusciante, Luigi (Frontiers in Plant Science, 2018)
The advent of new sequencing technologies is revolutionising the studies of ancient DNA (aDNA). In the last 30 years, DNA extracted from the ancient remains of several plant species has been explored in small-scale studies, contributing to understand the adaptation and migration patterns of important crops. More recently, NGS technologies applied on aDNA have opened up new avenues of research, allowing investigation of the domestication process on the whole-genome scale. Genomic approaches based on genome-wide and targeted sequencing have been shown to provide important information on crop evolution and on the history of agriculture. Huge amounts of next-generation sequencing (NGS) data offer various solutions to overcome problems related to the origin of the material, such as degradation, fragmentation of polynucleotides and external contamination. Recent advances made in several crop domestication studies have boosted interest in this research area. Remains of any nature are potential candidates for aDNA recovery and almost all the analyses that can be made on fresh DNA can also be performed on aDNA. The analysis performed on aDNA can shed light on many phylogenetic questions concerning evolution, domestication and improvement of plant species. It is a powerful instrument to reconstruct patterns of crop adaptation and migration. Information gathered can also be used in many fields of modern agriculture such as classical breeding, genome editing, pest management and product promotion. Whilst unlocking the hidden genome of ancient crops offers great potential, the onus is now on the research community to use such information to gain new insight into agriculture.